CORPORATE GOVERNANCE AND LEVERAGE ON TAX AGGRESSIVENESS: EMPIRICAL STUDY ON MINING COMPANIES IN INDONESIA - Vanesali, Laurensia; Kristanto, Ari Budi (International Journal of Social Science and Business, 2020)
This study aims to investigate the effect of corporate governance and leverage towards tax aggressiveness. The research data comprises 66 firm-year obtained from 11 mining companies during 2013-2018. They were sorted using a purposive sampling method. The hypotheses were tested using multiple regression analysis. The results indicate that institutional ownership and audit committee had a positive and significant effect on tax aggressiveness, the proportion of independent commissioners and audit quality had a negative and significant effect on tax avoidance, while leverage was not considered as a determinant of tax avoidance in Indonesian manufacturing firms.